A Developmental-Ecological Model of the Relation of Family Functioning to Patterns of Delinquency - Gorman-Smith, Deborah (Journal of quantitative criminology, 2000)
Person-centered approaches to understanding delinquent and criminal careershave identified several distinct pathways or patterns of delinquent behavior(Gorman-Smith et al., 1998; LeBlanc and Kaspy, in press; Loeber et al.,1991; Loeber et al., 1993). In addition, research suggests that there maybe etiological variations that correspond to these different pathways(Gorman-Smith et al., 1998). That is, there may be different configurationsof risk factors associated with different types of delinquent and criminaloffending. If this is so, understanding these relations can have importantimplications for intervention and prevention. However, there have been fewstudies that examine how the configuration of risk factors may vary inrelation to different delinquency pathways. The current study brings aperson-centered analysis to examine how patterns of family functioningrelate to patterns of offending. In addition, this study contextualizesthese relations by examining how these relations vary as a function ofcommunity setting. This study expands upon previous research that hasidentified four basic patterns of delinquent behavior among a sample ofminority male adolescents living in poor urban neighborhoods (Gorman-Smithet al., 1998).